Strategi pemenuhan hak pendidikan bagi semua anak oleh komunitas belajar qaryah thayyibah Kota Salatiga - Damayanti, Novia; P. H., Rima Vien; Triyanto, Triyanto (Academy of Education Journal, 2024)
The purpose of this research is to find out how Komunitas Belajar Qaryah Thayyibah strategy fulfills the right to education for children and to know what is the factors that influence the strategy and also the relationship between the strategy and civic participation. This study uses a qualitative approach with descriptive qualitative. Data collection uses observation, interviews, and document analysis. The results showed that the two strategies used by the Komunitas Belajar Qaryah Thayyibah, namely education fee waiver and a needs-based curriculum, were very good at helping fulfill the right to education for every child, especially children around the KBQT area. Based on the theory of community participation is also in line with what is done by KBQT. Indirectly, KBQT has realized civic participation quite well. What has been done by KBQT has assisted the government in fulfilling the right to education for every citizen, where through state laws it also opens up as many opportunities as possible for the community to participate in fulfilling the right to education.